Réponses

Meilleure réponse !
2013-01-07T00:06:22+01:00

Il faut dévelloper D= (4x +1)²-(3x-2) = (4x+1) ou (4x+1) (x+3)=0 ?? 

Car si c'est (4x+1) (x+3)=0

Il faut que tu fasse sa : X est un fois

4x X x  + 4x X3 +1 X x + 1 X 3= 

4x² + 12x + 1x + 3=

4x² + 13x+ 3. 

Mais sa ne donne pas 0 ..:/ 

2013-01-07T00:07:09+01:00

D= (4x+1)² - (3x-2)(4x+1)= 4x² +8X +1 -(12x² +3x- 8x -2)= 4x²+8x+1 -12x² -3x+8x+2=

D=-8x²+13x+3.

(4x+1)²  - (3x-2)(4x+1)= (4x+1)[4x+1-3x+2]=(4x+1)(x+3)

(4x+1)(x+3)=0 => 4x+1=0 ou x+3=0 donc x=-1/4 ou x=-3.